Relating the gospels: memory, imitation and the Farrer hypothesis - Eve, Eric (Library of New Testament studies, 2021)
Cover -- Contents -- Abbreviations -- 1 Introduction -- 2 Models, memory and Markan priority -- Elite, oral and scribal composition -- Memory -- The evangelists' purpose -- Markan priority -- Implications and working hypotheses -- 3 Transformational techniques -- Progymnasmata -- Compositional practices in previous Synoptic Problem scholarship -- Reordering and rearrangement -- Literary imitation -- 4 Significant similarities -- Significant verbal similarities in the triple tradition -- Significant verbal similarities in the double tradition -- Significantly similar beginnings -- Conclusion -- 5 Difficult differences -- Infancy and resurrection narratives -- Alternating primitivity -- Luke's non-use of Matthean additions to Mark -- Unpicking or 'minor disagreements' -- Conclusion -- 6 The order objection -- The problem -- Matthew's order -- Luke's order -- Conclusion -- 7 Conclusion -- Retrospect -- Known unknowns -- Prospects -- Bibliography -- Index of References -- Index of Authors.